The effects of perceived work overload on organizational commitment on employee turnover intention in automotive industry in Pahang - Qamarina, Aqilah; Ahmad Taufik, Nursal; Azim Azuan, Osman; Muhammad Rahimi Izhar, Redzuan (Universiti Utara Malaysia, 2023)
Employee turnover is a critical concern for organizations, as it can adversely affect service quality and incur substantial expenses. Drawing on the theoretical framework of social exchange theory, this study presents a model to examine the interconnections between turnover intentions, organizational commitment, and perceived task overload among employees in the automotive sector of Malaysia. Data was collected from 158 automotive industry professionals who voluntarily participated in the study. The proposed hypotheses were validated using structural equation modeling (SEM) via SmartPLS 4.0. The findings provide empirical support for the hypothesis that employees' perceptions of task overload directly influence their level of commitment to their respective organizations. Moreover, their perceived work overload, combined with organizational commitment and incentives, significantly impacts their turnover intentions, influencing their decision to leave their current positions. Surprisingly, organizational commitment was found to have no significant direct effect on turnover intention. This novel research offers a comprehensive model to manage turnover intention among automotive industry employees in Malaysia, utilizing organizational commitment as a mediating factor. The level of dedication demonstrated by employees towards their organizations plays a vital role in determining whether they will remain with the organization, even when they perceive their skills to be declining. These findings hold implications for both research and clinical practice, offering valuable insights for improving workforce readiness amidst the challenges posed by the industrial revolution 4.0.